Pemasaran produk Olahan Tahu/Tempe dan Perhitungan Harga Pokok Penjualan pada UMKM - Rahmat Yuliansyah; Rutinaias Haholongan; Krisnando Krisnando; Erizal Azhar; Bayu Pratama; Basyiruddin Nur; Andi Fuji (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta (BPJP - STEI), 2021)
Community Service (Abdimas) aims to provide understanding/skills for developing the marketing of processed products and understanding/skills in calculating the cost of goods sold for entrepreneurs of tofu/tempeh. In addition, this activity is also expected to create benefits for other participants. Community service activities in the form of counseling on how to develop the marketing of processed products and calculating the cost of goods sold tofu/tempeh as a promising business opportunity. Activities carried out on tofu/tempeh entrepreneurs in the North Cipinang Besar Village, went smoothly. Participants can develop skills according to changes in technology so that tofu/tempeh products can be more varied. Participants know the advantages and disadvantages of the tofu/tempeh product business from their business activities and increase their accounting knowledge in managing their business